Luxury After the Terror - Moon, Iris (Book collections on Project MUSE., 2022)
"Explores the production, circulation, and survival of French luxury after the death of Louis XVI by focusing on makers of decorative art objects who had strong ties to the monarchy and how they navigated the French Revolution"--